Establishing research priorities for Australian radiation therapists: what patient care priorities need to be addressed? - Halkett, Georgia; Cox, J.; Anderson, C.; Heard, R. (Blackwell Publishing Ltd, 2011)
Much of the research conducted in radiotherapy focuses on technology advances; however, research may also be warranted in the area of patient care. The aims of this paper are to (1) identify patient care-related research priorities in radiation therapy and (2) describe similarities and differences in radiation therapists' responses to research priorities related to patient care by subgroups revealed through cluster analysis. A Delphi process was used, examining problems in research that radiation therapists face. Three hundred and seventy-four problems were identified. These were translated into 53 research areas which were then prioritised. Participant subgroups were identified using a hierarchical cluster procedure. Agreement and disagreement between subgroups for the subscale of ‘Patient Care’ were analysed with ANOVA and post hoc Scheffe multiple comparisons. The three subgroups had varying degrees of research interest in patient care. The groups agreed on the importance of research in relation to patient care in reducing and managing side effects, patient education and support, and treatment techniques. However, there was disagreement about the importance of conducting research into the role of radiation therapists, radiation therapists communicating and educating patients, and psychosocial support. Further research is warranted to determine radiotherapy patients' priorities and improve evidence-based practice.